-4(x+2)+2=2(x+6)

Simple and best practice solution for -4(x+2)+2=2(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(x+2)+2=2(x+6) equation:


Simplifying
-4(x + 2) + 2 = 2(x + 6)

Reorder the terms:
-4(2 + x) + 2 = 2(x + 6)
(2 * -4 + x * -4) + 2 = 2(x + 6)
(-8 + -4x) + 2 = 2(x + 6)

Reorder the terms:
-8 + 2 + -4x = 2(x + 6)

Combine like terms: -8 + 2 = -6
-6 + -4x = 2(x + 6)

Reorder the terms:
-6 + -4x = 2(6 + x)
-6 + -4x = (6 * 2 + x * 2)
-6 + -4x = (12 + 2x)

Solving
-6 + -4x = 12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-6 + -4x + -2x = 12 + 2x + -2x

Combine like terms: -4x + -2x = -6x
-6 + -6x = 12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-6 + -6x = 12 + 0
-6 + -6x = 12

Add '6' to each side of the equation.
-6 + 6 + -6x = 12 + 6

Combine like terms: -6 + 6 = 0
0 + -6x = 12 + 6
-6x = 12 + 6

Combine like terms: 12 + 6 = 18
-6x = 18

Divide each side by '-6'.
x = -3

Simplifying
x = -3

See similar equations:

| X+6=-21x-10 | | 2d^2=162 | | Y=-6-5 | | X+1=2x-10 | | 3(y-2)-5y=-2(y+3) | | 13-s=65 | | -5x+6=-x+22 | | 7m+6-5=15 | | x^2+11x+28=o | | 3+2x=4x-21 | | -2(5s-5)-10=-2(8s+10)-3 | | 7(t+8.5)-5+4t= | | 5(r-4)=-10 | | Y=2(-2)+5 | | n/9=4 | | 7(t+8.5)-5+4= | | f*0.25=0.0625*2+2 | | 6x+9=39+3x | | 3y(y-2)-5y=-2(y+3) | | L+w=10+4(l-w) | | 25*x^2-30*x+9=81 | | 2x+5(3x-2)=8x+5 | | 0.62+p=62.87 | | b-12=-8 | | -12=a+6 | | .33c=-8 | | s-18=8 | | 1.5x-12=12 | | 6.5a+14=72.5 | | 10x^2-60-25x= | | 1.5(n-4.5)=12 | | 9w^2+24w+16= |

Equations solver categories